Stroke Serum Priming Modulates Characteristics of Mesenchymal Stromal Cells by Controlling the Expression miRNA-20a. Issue 8 (August 2016) - Kim, Eun Hee; Kim, Dong Hee; Kim, Hye Ree; Kim, Soo Yoon; Kim, Hyeon Ho; Bang, Oh Young
Transplantation of mesenchymal stem cells (MSCs) expanded with fetal bovine serum (FBS) has some limitations, including the requirement of a long culture period to obtain a sufficient amount of stem cells. Priming of MSCs with serum from patients with ischemic stroke (stroke serum) increased the proliferation rate and the neurorestorative capacity of MSCs. We hypothesized that this novel priming method increases the proliferation rate of MSCs via the regulation of microRNAs (miRs). Thus, we investigated miR profiling in stroke serum-primed MSCs and tested whether the regulation of certain miRs may affect the proliferation rate of rat MSCs. The proliferation rate of MSCs cultured with stroke serum was higher than that of MSCs cultured with normal serum or FBS. Using miR microarray analysis, we compared the miR expression profiles between MSCs cultured in FBS and in stroke serum. Among miRs associated with cell proliferation, miR-20a was most significantly increased. Similarly, miR-20a was increased in MSCs obtained from the bone marrow of stroke rats compared with MSCs from normal rats. Furthermore, the deregulation of miR-20a by the transfection of MSCs with pre-miR-20a or anti-miR-20a was significantly correlated with the increased proliferation rate of MSCs. The overexpression of miR-20a in MSCs cultured in FBS improved the proliferation rate, while the knockdown of endogenous miR-20a decreased the proliferation rate. In addition, miR-20a promoted proliferation by suppressing the expression of p21 cyclin-dependent kinase inhibitor 1 (CDKN1A). A dual-luciferase reporter assay showed that CDKN1A is a target of miR-20a. Our findings indicate that stroke serum priming upregulated the expression of miR-20a, which promoted MSC proliferation by regulating the cell cycle inhibitor p21 CDKN1A, and suggest the possible roles of priming methods in modulating the characteristics of MSCs by controlling the expression of miR in MSCs.